Effects of a Magnetic Field on Surface and Subsurface Drip Irrigation Water, Tomato Plants and Desert Sandy Soil Characteristics - Ahmed A. Al‐Othman; Doaa M. El‐Shinawy; Awad Ali Tayoush Oraiath; Abdallah Elshawadfy Elwakeel; Ahmed Z. Dewidar; Ahmed Elbeltagi; A. H. Hamza (Irrigation and Drainage, 2026)
This study, conducted in Shosha, Minia, Egypt, aimed to evaluate the effects of magnetically treated saline groundwater on both soil characteristics and the performance of tomato crops grown in arid sandy soils. The influence of magnetic fields on water quality was first assessed to determine its suitability for irrigation. Subsequently, the combined effects of MWT with different irrigation methods—namely, surface drip irrigation (SDI) and subsurface drip irrigation (SSDI)—as well as system design types (closed vs. open systems), were examined to understand their impact on soil health and chemical properties under saline conditions. Magnetic treatment significantly improved water quality by reducing sodium and chloride accumulation in the root zone and decreasing the Na/Cl ratio from 1.07 to 0.98. This facilitated salt leaching and reduced plant salt stress. Treated water also lowered soil electrical conductivity (EC) and soluble ion concentrations while increasing soil moisture retention and field capacity. SSDI with magnetised water achieved a wetted soil volume of 94,500 cm 3 —vastly greater than 6720 cm 3 under unmagnetised open SDI. Emitter clogging ratio (ECR) was reduced from 12% to 5%, improving system reliability. Application efficiency rose from 89% to 97%, and emission uniformity improved from 90% to 96%.

Towards sustainability and circular economy: conceptual design model for the water-energy-food nexus in Ferdaws Village, Western Desert, Egypt - Noha M. Mashaal; Mohamed A. Abdelzaher; Mohamed M. Awad; Khalid Z. Elwakeel; Ahmed A. Hassan (Innovative Infrastructure Solutions, 2025)
Sustainable management of natural resources is a pressing global challenge that requires the prevention of loss and waste. Egypt is facing an acute water crisis due to insufficient water supplies throughout the country. To address this issue, it is essential to implement a range of solutions to improve the situation. This study aims to alleviate the stress on multiple resources and environmental impacts in one of Egypt's earliest reclaimed areas (Wadi El-Natrun, Western Desert), by applying systematic modeling to achieve sustainable development objectives and mitigate resource stress. To promote a more sustainable and resilient future, a pilot model ecovillage has been designed for a community of three thousand inhabitants, promoting integrated resource management and considering the Water-Energy-Food (WEF) nexus concept. The ecovillage design incorporates collaborative engagement of groundwater reservoirs for water supply, agricultural production for food demands, power generation, and community sensitivity. Evaluating key aspects related to water supply, power generation, agricultural production, and environmental impact within the proposed pilot design aims to provide insights into the complex interactions among these systems. A four-step methodology for evaluating and implementing the nexus at a local level, which includes identifying linkages, mapping interconnections, focusing on core foundations, and applying the findings to improve project execution was investigated. An understanding of the WEF nexus, demonstrating how such frameworks can enhance the management of scarce resources was provided. The “TORAY DS2” design is employed to analyze model parameters and quantify their values. The study’s findings aim to support decision-makers and stakeholders in developing effective strategies to navigate the complexities of the WEF Nexus, promoting optimal resource management. These findings are promising, indicating a low environmental risk while aligning with both the WEF Nexus and the Sustainable Development Goals.

Foliar Nourishment with Different Potassium Sources to Maximize Yield Through Improving Nutrient Uptake in Citrus Aurantifolia Trees Grown in Potassium-Deficient Soil - Ahmed A. M. Awad; Hamdy A. Z. Hussein; Asmaa G. A. Abd El Samad; Hussein E. E. Belal; Hamada R. Beheiry (Journal of Soil Science and Plant Nutrition, 2024)
Purpose: Based on its crucial regulatory role in several biochemical processes, potassium (K) is considered to greatly influence fruit yield and quality. Methods: Two field experiments were carried out in two seasons (2021 and 2022) to explore the response of lemon (Baladi cv.) trees grown in K-deficient soil to four different K fertilizer sources applied individually as a foliar spray. K citrate (KC 1 = 1.3 vs. KC 2 = 2.6 g L − 1 ), K nitrate (KN 1 = 1.5 vs. KN 2 = 3.0 g L − 1 ), K tartrate (KT 1 = 1.5 vs. KT 2 = 3.0 g L − 1 ), and K thiosulfate (KS 1 = 1.25 vs. KS 2 = 2.5 g L − 1 ) were applied three times, and the treated trees were compared with untreated trees. This study was established with a randomized complete block design (RCBD) using four replicates. Results: The findings revealed that the KC treatment, regardless of dosage, showed clear superiority in terms of the values for the leaf phosphorus (%), manganese, and zinc contents (mg kg − 1 ), as well as fruit firmness, fruit dry matter, and total soluble solids in both seasons. In second place was the KT treatment, which yielded the best values for fruit length and width in 2021, the best values for leaf nitrogen and iron contents and fruit weight and volume in 2022, and the best values regarding variable fluorescence by maximum fluorescence, relative chlorophyll content (SPAD readings), the photosynthetic performance index, total acidity, and vitamin C in both seasons. Furthermore, the highest total lemon yield and leaf potassium contents were achieved with the KN treatment in both seasons. The heat map illustrating that most of the studied characteristics were positively and significantly correlated with total lemon yield (TLY). Conclusions: The KN treatment, closely followed by the KC treatment, is regarded to be the best treatment for most of the studied trails.

The vegetation around the foothills of the Hijaz Mountains, Saudi Arabia - Nick Hofland; Mohamed Z. Hatim; Jacob Thomas; John A. M. Janssen; Awad S. Alharti; Ahmed H. Alfarhan; Abdulrahman A. Alatar; Joop H. J. Schaminée; Mohamed A. El-Sheikh (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)
Despite Saudi Arabia being an interesting area from a floristic perspective, its vegetation is still relatively poorly studied. This certainly applies to the Hijaz Mountains and adjacent coastal zones. We aim to describe the flora and vegetation of the foothills of the Hijaz Mountains regarding the environmental conditions. Hijaz Mountains and adjacent coastal zones, Saudi Arabia. We studied the vegetation at the Hijaz Mountains’ foothills along two transects of vegetation surveys, one along the coast and one more inland. In addition, soil samples were taken and analyzed for soil texture, pH, electrical conductivity, organic matter, calcium carbonate and the concentration of the elements N, Na, K, Ca, Mg, Fe and Mn were determined. We calculated the data clustering tendency (Hopkins’ test analysis) and its optimal number of clusters (Elbow method). We used modified TWINSPAN to cluster the data and validated the resulting communities using the Silhouette algorithm. Seven plant communities resulted, each one dominated by a different plant species, namely: Haloxylon salicornicum , Lycium shawii , Senegalia hamulosa , Vachellia tortilis , Zygophyllum coccineum , Vachellia flava and Stipagrostis plumosa , and were described based on their floristic composition and could be further grouped into three vegetation clusters. The communities had varying ranges of occurrence in the study area, some dominating certain sections, with latitude and altitude being the biggest distinguishing environmental variables between the communities. We present a description of the vegetation of the Hijaz Mountains foothills. Our study is considered an important basis for decision-making of nature conservation and in-depth surveys of the area. Graphic abstract

Therapeutic effect of dithiophenolato chitosan nanocomposites against carbon tetrachloride-induced hepatotoxicity in rats - Nadia Z. Shaban; Ahmed M. Aboelsaad; Doaa Awad; Shaymaa A. Abdulmalek; Shaban Y. Shaban (Environmental Science and Pollution Research, 2022)

An acetylated derivative of vitexin halts MDA-MB-231 cellular progression and improves its immunogenic profile through tuning miR- 20a-MICA/B axis - Aya R. Awad; Rana A. Youness; M. Ibrahim; Amira Abdel Motaal; Hesham I. El-Askary; Reem.A. Assal; Mohamed Z. Gad (Natural Product Research, 2021)

Two new proanthocyanidin trimers isolated from Cistus incanus L. demonstrate potent anti-inflammatory activity and selectivity to cyclooxygenase isoenzymes inhibition - K. A. Mansoor; K. Z. Matalka; F. S. Qa’dan; R. Awad; M. Schmidt (Natural Product Research, 2016)

Effect of some pyrimidine compounds on rat brain monoamine oxidase-B in vitro - Nadia Z. Shaban; Mamdouh S. Masoud; Mai A. Mawlawi; Doaa Awad; Omayma M. Sadek (Journal of Physiology and Biochemistry, 2012)